Gambaran Tanda Tanda Vital pada Pasien Sectio Caesarea dengan Anastesi Spinal di RSI Muhammadiyah Pekajangan Pekalongan - Teti Indriani; Dafid Arifiyanto; Neti Mustikawati (Prosiding University Research Colloquium, 2022)
Backgroud : The prevalence of Sectio Caesarea in Indonesia reaches 17,6%. Sectio Caesarea in an artificial birth in which the fetus is delivered through an incision. The surgical process requires anaesthesia. Spinal anaesthesia used in Secto Caesarea causes complications such as hypotension, bradycardia, hypoxia and hypothermia. Accordingly, patient’s vital sign must be observed during preoperative, intraoperative and postoperative. Objective : The study ised a descriptiver method wit an observasional approach, data collection used an observation sheet for vital sign. The study involved 40 Sectio caesarea patients with spinal anaesthesia at RSI PKU Muhammadiyah Pekajangan Pekalongan. Result : The result show that most of the Sectio caesarea patients with spinal anaesthesia aged 20-35 years (87,5%), had a high school education level (42,5%) and mltigravida (72,5%). Hypotension and bradycardia occurred 5 minutes after spinal anaesthesia. The mean systolic blood pressure was 89,28 mmHg, diastolic 59,35 mmHg, pulse 59,53 times/minute. Hypothermia occurred 15 minutes after spinal anaesthesia with an average temperature of 34,89°C. Conclusion : observastion of vital signs is very important in Sectio caesarea patiens with spinal anaesthesia at RSI PKU Muhammadiyah Pekajangan Pekalongan.